Analisis Deiksis dalam Film Fall (2022) - Erviolin Septi Putriana; Dyah Nugrahani; A.B. Prabowo K.A (Jurnal Penelitian Multidisiplin Ilmu, 2023)
This study aims to determine the types of deixis and references used by the main character in the FALL (2022) movie, and to determine the dominant deixis used by the main character in FALL (2022) movie The study employs qualitative methods to gather data from the main character's spoken sentences from the FALL (2022) Movie, which were downloaded from the internet. The study revealed that 608 deixis expressions were utilized. The expression deixis is divided into five types of deixis, namely 424 person deixis, 11 place deixis, 149 time deixis, 21 social deixis, and 3 discourse deixis. The references found in this study are, person deixis found are I, me, my, we, and our as the first person deixis; you and your as second person deixis; it, she, he, him,and they, as third-person deixis; the place deixis found are here, that, these, and this; the time deixis found now,everyday, a weeks ago, morning, today, turn, this weekend, yesterday, night; the social deixis found dad, your mother, my husband, my cherry pie, ; and the last discourse deixis found is that and this. The dominant deixis used by the main character in the FAL (2022) Movie is person deixis.